Assessing genetic diversity of wild and hatchery samples of the Chinese sucker (Myxocyprinus asiaticus) by the mitochondrial DNA control region. (3rd March 2016) - Wu, Jiayun; Wu, Bo; Hou, Feixia; Chen, Yongbai; Li, Chong; Song, Zhaobin
Abstract: To restore the natural populations of Chinese sucker ( Myxocyprinus asiaticus ), a hatchery release program has been underway for nearly 10 years. Using DNA sequences of the mitochondrial control region, we assessed the genetic diversity and genetic structure among samples collected from three sites of the wild population as well as from three hatcheries. The haplotype diversity of the wild samples ( h = 0.899–0.975) was significantly higher than that of the hatchery ones ( h = 0.296–0.666), but the nucleotide diversity was almost identical between them ( π = 0.0170–0.0280). Relatively high gene flow was detected between the hatchery and wild samples. Analysis of effective population size indicated that M. asiaticus living in the Yangtze River has been expanding following a bottleneck in the recent past. Our results suggest the hatchery release programs for M. asiaticus have not reduced the genetic diversity, but have influenced the genetic structure of the species in the upper Yangtze River.